PEMBELAJARAN BAHASA INGGRIS MANDIRI DAN PENGUASAAN KOSAKATA MAHASISWA S1 STIKES HUSADA JOMBANG - Nur Fadilla, Atika (PRIMA WIYATA HEALTH, 2025)
Background: Self-regulated learning is a learning process that requires specific strategies or methods to run optimally and be carried out independently. However, students have encountered several learning difficulties, one of which is vocabulary mastery. Objectives: This study aimed to find out whether a significant correlation between students’ self-regulated learning and vocabulary mastery. Methods: The researchers used a quantitative method with a correlation design to analyze the data. The participants were 37 seventh-semester nursing students from the College of Health Science of Husada Jombang. The instruments used were tests and questionnaires. To analyze the correlation, the researchers used a standard correlation coefficient interpretation using SPSS version 26.0 for Windows. Results: The findings of the study showed that the data it was found all the variables had a significant (sig.) value of 0.000. Then, the result showed that the correlation coefficient between self-regulated learning and vocabulary mastery was 0.730. Based on the result above, although the correlation is high, the level of significance is sufficient to reject the null hypothesis (Ho), which means Ha is accepted. Conclusion: It can be concluded that there is a correlation between English self-regulated learning and vocabulary mastery.